PELAKSANAAN EKSTRAKURIKULER TAHFIDZUL QUR’AN DI MA NURUL ULUM PUTRI KEBONSARI MALANG - Lula Fatmawati; Anwar Sa dullah; Imam Safii (VICRATINA, 2022)
We as Muslims are required to learn what is contained in the Qur'an not only that wealso have to be able to read the Qur'an properly and correctly. However, with thepassage of time, many people today are memorizing the Qur'an, such as the exampleof MA Nurul Ulum who programmed the extracurricular tahfidzul qur'an. So studentswho wish to take extracurricular activities are welcome and not required for studentswho want to study there. The researcher formulates the problem, namely how toimplement tahfidzul qur'an extracurricular and what are the supporting andinhibiting factors for tahfidzul qur'an extracurricular at MA Nurul Ulum. The purposeof this study was to describe how the implementation of tahfidzul qur'anextracurricular and to describe the supporting and inhibiting factors of tahfidzulqur'an extracurricular at MA Nurul Ulum. In this study, researchers used qualitativeresearch methods. This study uses several data collection techniques, namelyinterviews, observation and documentation. Based on interviews, observations andalso documentation, it has been found that the implementation of the extracurriculartahfidz Al-Qur'an is carried out well.